PEMANFAATAN PLATFORM RUANG GTK SEBAGAI MEDIA PENGEMBANGAN KEPROFESIAN BERKELANJUTAN BAGI GURU - Hasnawi Hasnawi; Saifuddin Saifuddin; Zarkasyi Zarkasyi; Marnita Marnita (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2026)
ABSTRAK Pengembangan Keprofesian Berkelanjutan (PKB) merupakan aspek fundamental dalam peningkatan profesionalisme guru di era digital. Penelitian ini bertujuan untuk menganalisis pemanfaatan platform Ruang GTK sebagai media pengembangan keprofesian berkelanjutan bagi guru. Penelitian menggunakan pendekatan kualitatif dengan metode studi literatur. Data diperoleh dari dokumen utama serta berbagai literatur ilmiah dari para ahli pendidikan Indonesia. Hasil penelitian menunjukkan bahwa platform Ruang GTK berperan strategis dalam meningkatkan akses pelatihan, memperkuat komunitas belajar, dan meningkatkan kompetensi digital guru. Namun, implementasinya masih menghadapi kendala seperti keterbatasan infrastruktur, rendahnya literasi digital, serta motivasi guru yang belum optimal. Oleh karena itu, diperlukan strategi integratif berupa penguatan kebijakan, peningkatan literasi digital, serta pemerataan akses teknologi guna mengoptimalkan PKB berbasis digital. ABSTRACT Professional Development (Continuous Professional Development/CPD) is a fundamental aspect in improving teacher professionalism in the digital era, which demands adaptive skills toward technological developments and curriculum changes. In this context, this study aims to analyze the utilization of the Ruang GTK platform as a medium for teachers’ continuous professional development. The focus of the study is directed at examining the role, benefits, and implementation challenges of Ruang GTK in supporting the ongoing improvement of teachers’ competencies. This study uses a qualitative approach with a literature review method. The research stages were carried out through the collection of data from primary documents, scientific journal articles, and various relevant literature from Indonesian education experts within the last five years. The data were then analyzed through reduction, categorization, and synthesis processes to obtain a comprehensive overview of the utilization of Ruang GTK in CPD. This analytical process was conducted to identify patterns, gaps, and trends in previous research findings. The results show that the Ruang GTK platform plays a strategic role in improving access to training, strengthening learning communities, and enhancing teachers’ digital competencies. In addition, Ruang GTK also supports flexible teacher learning through a digital system that enables independent and continuous professional development. However, its implementation still faces several challenges, such as infrastructure limitations, low digital literacy, and suboptimal teacher motivation in participating in CPD programs. Based on these findings, it can be concluded that the optimization of digital-based CPD requires an integrated strategy through strengthened policies, improved teachers’ digital literacy, and equitable access to technology so that the utilization of Ruang GTK can be more effective and sustainable.